ICTE 2013 : Proceedings of the Fourth International Conference on Transportation Engineering : October 19-20, 2013, Chengdu, China - Peng, Qiyuan, editor; Wang, Kelvin C.P., editor (Reston, Virginia : American Society of Civil Engineers, 2013)
Single-Pier Bridge Lateral Stability Analysis in Dynamic Load Conditions -- Bus Arrival Time Prediction Based on GPS Data -- Application of Improved Particle Swarm Algorithm on Optimization of Dispatching Decision of Wagon Flows in Railway Hubs -- Automatic Control Process Analysis on Railway Cargo Handling Conditions under E-Commerce -- Cluster Analysis of Mineral Resources Based on AHP -- Response of Prefabricated Slab Track to Failed CA Mortar -- Optimization of Decision Making on Railway Emergency Plans with DEA and ANP -- Setting Mode of Comprehensive Maintenance Skylight to Zhengzhou-Xi'an High-Speed Railway -- Outline of Research on High-Speed Railway Dispatching Command System -- Contradiction Analysis and Freight Capacity Promotion Measures of Mixed Passenger and Freight Transportation During the Spring Festival -- Optimization Model for Locating Electric Bus Charging Stations. Influencing Factor Analysis of Freeway Work Zone Capacity and Its Estimation Model -- Research on Urban Slow-Traffic Spatial Environment's Detail Optimization -- Study of Location and Layout for Emergency Resources Based on Weight of Risk -- SPSS-Based Analysis of Factors Affecting Road Traffic Safety -- Seismic Frequency Spectrum Character Analysis Based on Wavelet Method -- Evaluation of Filling Ruts to Micro-Surface Technology Based on Full-Scale Accelerated Pavement Test -- Effect of PC Steel Bar's Failure on the Stress Distribution in Track Plate -- Analysis of Individual Ventilation Effects of Down Steps in Highway Gas Tunnel Construction with the Up-and-Down-Steps Method -- Deterrent Effect Mechanism of Traffic Electronic Enforcement -- Road Traffic Dynamic Optimal Strategy Based on Fuzzy Set Theory -- Problem-Identification Evaluating Model of Coordinated Signal Control on Arterial Streets -- Dynamics Simulation of Heavy Haul Locomotive with Radial Bogie -- Novel Method of Detecting Position in a Maglev Vehicle Using Collection Rail Characteristics -- Application of Wavelet Theory in Subway Vibration Analysis -- Transfer Organizational Mode Simulation Based on Cellular Automata Model. Strategy and Optimization of Empty Container Transportation -- Integrated Optimization Model for Highway Operating Energy-Saving Technology -- Calibration Model for the Visual System of Advanced Driving Simulators -- Evaluation of Efficiency of Resource Allocation in the Highway Transportation System with Data Envelopment Analysis -- Safety Evaluation of a Transfer Station Based on Gray Incidence Appraisal Method -- Stochastic Traffic Assignment Algorithm Based on Probit Model -- Influence of Different Methods Obtaining Air-Gap Change Rate on the Stability of Electromagnetic Suspension System in Maglev -- Analysis of Low-Noise Parameters of Slab Structures in High-Speed Railway -- Adaptability Evaluation of Comprehensive Passenger Transport Centers -- Organization Pattern of Railway Express Freight Transportation. Dynamic Logistics Network Optimization Model in Manufacturers' Joint Ventures -- Real-Time, Multi-Factors-Coupled Early Warning Model in Water Transportation Safety -- Radial Basis Function Neural Network Predicting of Resilient Modulus for Shanxi Subgrade Soils -- Application Effect Assessment of Highway Tunnel Luminescence Guiding Facilities -- Trip Travel Time Distribution Prediction for Urban Signalized Arterials -- Damage Detection in Roads and Bridges Based on Modal Strain Energy Method -- Electric Multiple Units Train Traction Calculating System -- Dynamic Performance of Unbonded Pre-Stressed Steel Bar in CRTS I Ballastless Slab Track under Train Load -- Weekend Travel Behavior Analysis and the Improvement Method of Origin Transport Service Level -- Traffic Demand Forecasting Method for Auto Parts Industrial Park Considering Both the Production Location Impact and Mixed Traffic Characteristics -- Optimization of Empty Container Allocation in Depots with the Participation of Freight Forwarders -- Multi-Objective Emergency Resources